Pengaruh Media PowerPoint terhadap Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPS - Rahayu, Sri; Surasni, Surasni; Nanda Akhmad Romadhon, Dwi; Nofriansyah, Nofriansyah; Dahlan, Dadang (Jurnal Riset Pendidikan Ekonomi, 2024)
This study aims to determine whether the use of PowerPoint media in learning can improve the learning outcomes of Social Studies on the topic of International Trade for class IX B students at SMPN 21 Tanjung Jabung Timur. This research employs Classroom Action Research (CAR) methods with 34 students as subjects. The variables examined include learning outcomes and the implementation of the learning scenario over two cycles. The results indicate that (1) there was an increase in student learning outcomes from an average score of 71.47 with a classical mastery of 47% in cycle I to an average score of 82.20 with a classical mastery of 88% in cycle II. It can be concluded that there is an improvement in student learning outcomes of 88%, categorized as "high," after the use of PowerPoint media. Cycle I did not achieve classical mastery (53%), but in Cycle II, classical mastery was achieved at 88%, demonstrating a significant increase from 53% to 88%.